Answer:
542
Step-by-step explanation:
-3, 2, 7, 12
-3 + x = 2 x = 5
2 + x = 7 x = 5
7 + x = 12 x = 5
If you want to find the 3rd term in the sequence and you start with the first number, then you do this:
-3 + (2 * 5) = -3 + (10) = 7
The same goes for the 110th term:
-3 + (109 * 5) = -3 + (545) = 542
The formula to find the nth term is:
f(n) = n(0) + (n-1) * 5
Suppose n(0) = -3 then
f(110) = -3 + {(110-1) * 5}
f(110) = -3 + {(109) * 5}
f(110) = -3 + (545) = 542
You can simplyfy f(n) = n(0) + (n-1) * 5
f(n) = n(0) + (n-1) * 5
f(n) = n(0) + (5n-5)
f(n) = n(0) + 5n - 5
f(110) = -3 + (5 * 110) - 5
f(110) = -3 -5 + (550)
f(110) = - 8 + 550
f(110) = 542